Pengaruh Microteaching dan Dukungan Teman Sebaya terhadap Minat Mahasiswa Pendidikan Administrasi Perkantoran Universitas Negeri Jakarta Menjadi Guru - Imel Ahmarita Meliana; Marsofiyati Marsofiyati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This study aims to see the influence of microteaching and peer support on students' interest in becoming teachers in Office Administration Education students of the State University of Jakarta 2022. The research approach used is quantitative through surveys with online questionnaire distribution. Data processing uses the Statistical Package for Social Sciences (SPSS) application. From the test results, it was found that partially microteaching directly affected students' interest in becoming teachers, this was evidenced by a significant value of 0.025. In addition, partially, peer support did not affect students' interest in the teaching profession, this was evidenced by a significant value of 0.268. Meanwhile, simultaneously microteaching and peer support did not simultaneously affect interest in becoming a teacher, this was evidenced by a significant value of 0.078. In addition, the results were also strengthened by the results of the determination coefficient test which showed that the two independent variables only explained 14.3% of the dependent variables.